Motivasi dalam mengikuti kegiatan ekstrakurikuler bolatangan untuk siswa SMA/SMK/MA di Kabupaten Demak 2020 (Indonesian Journal for Physical Education and Sport, 2022)
Demak Regency has consistent achievements in the sport of handball, this can not be separated from the handball extracurricular activities held by SMA/SMK/MA in Demak Regency. Therefore, the aim of this researcher is to understand how high the motivation is in participating in extracurricular handball activities for SMA/SMK/MA students in Demak Regency 2020. The approach used is descriptive qualitative. The locations and areas studied were SMAN 3 Demak, SMKN 1 Demak, SMKN 2 Demak, SMAN 1 Karangtengah, MA Al-Anwar, SMK Nusa Bangsa. The results of this study are the motivation in participating in handball extracurricular activities for high school / vocational / MA students in Demak Regency 2020, it is known that students' intrinsic motivation in participating in handball extracurricular activities in Demak Regency is in the high category with a percentage of 56.36%. Each indicator in the intrinsic factor, the indicator gets the highest percentage with a percentage reaching 43.64%. Then for the extrinsic motivation of students in participating in handball extracurricular activities in Demak Regency, it is included in the high category with a percentage of 38.18%. Each indicator in the intrinsic motivation factor, the community indicator gets the highest percentage with a percentage reaching 47.28%.